Profil Kemampuan Pck (Pedagogical Content Knowledge) dan Kognitif Calon Guru Pendidikan Fisika Pada Pembelajaran Fisika Inti - Siti Nahria Hasan (Peneliti.net, 2023)
The teacher is the most important component in learning. So that a teacher is required to have pedagogic abilities and master the material (content). These two abilities are often combined into new knowledge called Pedagogical Content Knowledge (PCK). Therefore, this research was conducted with the aim of knowing the initial profile of the PCK and cognitive abilities of Physics teacher prospective students. The method used in this study was descriptive qualitative with a multiple choice test instrument to analyze and describe the initial profile of the PCK and cognitive abilities of prospective physics teachers in core physics learning. The subjects of this study were 18 students of the Physics Education Study Program even semester 2022/2023. Based on the research, it can be concluded that in several indicators, the pedagogical knowledge of prospective teacher students is still weak and there needs to be improvement, especially in determining appropriate learning strategies. Regarding knowledge of core physics material, students still experience many misconceptions as shown by the low average scores of almost all indicators.